SPORTS PERFORMANCE OF THE UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS IN TRUJILLO COLLEGE GAMES 2006 AND TACNA 2008 - Borda Hurtado, Jaime (2014)
This investigation examines the participation of students from the Universidad Nacional Mayor de San Marcos, in the XVII Trujillo National University Sports Games in 2006 and the XVIII Tacna National University Sports Games in 2008. The main goal was to identify the percentage difference in UNMSM sports performance in the two competitions as well as to analyze the infrastructure and sports equipment. Training and athletes are also important in this investigation. As a result of this investigation there are many suggestions such as the possibilities of infrastructure improvement, health care and recreation.